1997
DOI: 10.1113/expphysiol.1997.sp004005
|View full text |Cite
|
Sign up to set email alerts
|

The validity of the recollection technique in micropuncture experiments on the rat kidney

Abstract: SUMMARYWe tested the accuracy of the micropuncture technique by performing total collections of tubular fluid followed by immediate recollections from the same site. We studied thirty-one Wistar rats under different conditions of hydration and during maintenance infusions. To assure constancy of body fluid volumes the experiments were performed during continuous reinfusion of urine. When subdivided according to different physiological conditions and sampling sites, the results for the paired collection-recolle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
1

Year Published

1997
1997
1998
1998

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 13 publications
3
6
1
Order By: Relevance
“…However, we considered it more accurate to perform our calculation with raw uncorrected data, without resorting to complex recalculations based on assumptions which might be different among animals and tubules. The reader can evaluate the experimental error, which is consistent with that specifically measured and analysed by us (Romano et al 1997). Figure 4 reports the changes (A) in inflow on switching from control conditions to the experimental period of double collection, on the abscissa, plotted against the paired changes in reabsorption, on the ordinate.…”
Section: Resultssupporting
confidence: 71%
See 2 more Smart Citations
“…However, we considered it more accurate to perform our calculation with raw uncorrected data, without resorting to complex recalculations based on assumptions which might be different among animals and tubules. The reader can evaluate the experimental error, which is consistent with that specifically measured and analysed by us (Romano et al 1997). Figure 4 reports the changes (A) in inflow on switching from control conditions to the experimental period of double collection, on the abscissa, plotted against the paired changes in reabsorption, on the ordinate.…”
Section: Resultssupporting
confidence: 71%
“…Therefore, the relationship between reabsorption and filtration should be different, in conditions where the GTB is expressed, from that observed in conditions where these changes are random and attributable to experimental errors in measurements, as during collection-recollection sampling. Therefore we compared, by covariance analysis, the present data with the relationship between changes in filtration and reabsorption measured in 147 collection-recollection pairs previously obtained in the proximal tubule (Romano et al 1997). The covariance analysis demonstrates that the slopes are not different (P > 0.08).…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…However, we have demonstrated that the dierence between distal and proximal measurements was due to the technique of collection per se, such that they disappeared with an improved technique (Bartoli and Earley 1973). Subsequently, we have consistently reproduced those results (Bartoli et al 1996a, b;Romano et al 1995Romano et al , 1997, and so have others (Kirchner 1985;Xie et al 1990; Shirley and Walter 1991). It has been suggested that it is also possible that the proximal¯uid collection may result in undue manipulations of intratubular pressure, leading to spurious elevations of SNGFR (Brenner and Daugharty 1972).…”
Section: Introductionsupporting
confidence: 74%
“…Thus, we have found that simple experimental design is suitable to examine the reliability of the sampling technique, by comparing the data with the paired measurements of collection and immediate recollections from the same proximal sites (Romano et al 1997).…”
Section: Introductionmentioning
confidence: 99%